Protection of Irf5-deficient mice from pristane-induced lupus involves altered cytokine production and class switching - Feng, Di (2012)
Polymorphisms in the transcription factor interferon (IFN) regulatory factor 5 (IRF5) have been identified that show strong association with increased risk of developing the autoimmune disease systemic lupus erythematosus (SLE). A potential pathologic role for IRF5 in SLE development is supported by the fact that increased IRF5 mRNA and protein abundance are observed in primary blood cells of SLE patients that correlate with increased risk of developing the disease. Here, we demonstrate that IRF5 is required for pristane-induced SLE via its ability to control multiple facets of autoimmunity. We show that IRF5 has a distinct influence on pathological hypergammaglobulinemia and provide evidence for its role in regulating IgG1 class switching and antigen specificity. Examination of in vivo cytokine expression (and autoantibody production) identified an imbalance in Irf5(−/−) mice favoring Th2 polarization. In addition, we provide clear evidence that loss of Irf5 significantly weakens the in vivo type I IFN signature critical for disease pathogenesis in this model of murine lupus. Together, these findings demonstrate the global effect that IRF5 has on autoimmunity and provides significant new insight into how overexpression of IRF5 in blood cells of SLE patients may contribute to disease pathogenesis.